A Simple and Scalable Process for the Differentiation of Retinal Pigment Epithelium From Human Pluripotent Stem Cells - Maruotti, Julien (AlphaMed Press, 2013)
Age-related macular degeneration (AMD), the leading cause of irreversible vision loss and blindness among the elderly in industrialized countries, is associated with the dysfunction and death of the retinal pigment epithelial (RPE) cells. As a result, there has been significant interest in developing RPE culture systems both to study AMD disease mechanisms and to provide substrate for possible cell-based therapies. Because of their indefinite self-renewal, human pluripotent stem cells (hPSCs) have the potential to provide an unlimited supply of RPE-like cells. However, most protocols developed to date for deriving RPE cells from hPSCs involve time- and labor-consuming manual steps, which hinder their use in biomedical applications requiring large amounts of differentiated cells. Here, we describe a simple and scalable protocol for the generation of RPE cells from hPSCs that is less labor-intensive. After amplification by clonal propagation using a myosin inhibitor, differentiation was induced in monolayers of hPSCs, and the resulting RPE cells were purified by two rounds of whole-dish single-cell passage. This approach yields highly pure populations of functional hPSC-derived RPE cells that display many characteristics of native RPE cells, including proper pigmentation and morphology, cell type-specific marker expression, polarized membrane and vascular endothelial growth factor secretion, and phagocytic activity. This work represents a step toward mass production of RPE cells from hPSCs.